Pengaruh Islamic Lifestyle dan Islamic Branding Terhadap Keputusan Masyarakat Kota Cirebon Dalam Menggunakan Produk Perbankan Syariah - Prayogi Hasan; Rita Kusumadewi; Diana Djuwita; Budi Rusdian (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2025)
The rapid growth of Islamic banking in Indonesia is inseparable from the increasing public awareness of the importance of using halal products so that it changes people's lifestyles into an Islamic lifestyle or Islamic Lifestyle and marketing efforts made by Islamic Banking through Islamic Branding which can increase people's decisions to use Islamic banking products. The increasingly popular Islamic Lifestyle and Islamic Branding are considered keys that can contribute to increasing decisions to use Islamic banking products. Thus, this study aims to find the influence of Islamic lifestyle and Islamic branding on the decision to use Islamic Banking products in the Cirebon City Community. This study uses a quantitative approach with a field research method (Field Research), the sampling technique is carried out using a non-probability sampling method with a purposive sampling type. Thus it can be seen that the sample in this study amounted to 100 respondents. The data analysis technique in this study was analyzed using multiple linear regression using the IBM SPSS Statistics version 30 application. The results of the study indicate that the Islamic lifestyle variable has a positive and significant influence on the decision to use Islamic Banking products with a partial influence of 14.87%. The Islamic branding variable has a positive and significant influence on the decision to use Islamic Banking products with a partial influence of 11.37%. The results of the simultaneous test (F test) show that the Islamic lifestyle and Islamic branding variables have a positive and significant influence on the decision to use Islamic Banking products with a simultaneous influence of 26.3%.